ACYL-ACYL CARRIER PROTEIN DESATURASE2 and 3 Are Responsible for Making Omega-7 Fatty Acids in the Arabidopsis Aleurone . Issue 1 (26th July 2016) - Bryant, Fiona M.; Munoz-Azcarate, Olaya; Kelly, Amélie A.; Beaudoin, Frédéric; Kurup, Smita; Eastmond, Peter J.
Abstract : Two acyl-acyl carrier protein desaturases are responsible for the tissue-specific production of high levels of omega-7 monounsaturated fatty acids in Arabidopsis aleurone cells. Abstract: Omega-7 monounsaturated fatty acids (ω-7s ) are specifically enriched in the aleurone of Arabidopsis ( Arabidopsis thaliana ) seeds. We found significant natural variation in seed ω-7 content and used a Multiparent Advanced Generation Inter-Cross population to fine-map a major quantitative trait loci to a region containing ACYL-ACYL CARRIER PROTEIN DESATURASE1 ( AAD1 ) and AAD3 . We found that AAD3 expression is localized to the aleurone where mutants show an approximately 50% reduction in ω-7 content. By contrast, AAD1 is localized to the embryo where mutants show a small reduction in ω-9 content. Enzymatic analysis has previously shown that AAD family members possess both stearoyl- and palmitoyl-ACP Ɗ 9 desaturase activity, including the predominant isoform SUPPRESSOR OF SALICYLIC ACID INSENSITIVE2. However, aad3 ssi2 aleurone contained the same amount of ω-7s as aad3 . Within the AAD family, AAD3 shares the highest degree of sequence similarity with AAD2 and AAD4. Mutant analysis showed that AAD2 also contributes to ω-7 production in the aleurone, and aad3 aad2 exhibits an approximately 85% reduction in ω-7s . Mutant analysis also showed that FATTY ACID ELONGASE1 is required for the production of very long chain ω-7s in the aleurone. Together, these data provide genetic evidence that the ω-7 pathway proceeds via Ɗ 9 desaturation of palmitoyl-ACP followed by elongation of the product. Interestingly, significant variation was also identified in the ω-7 content of Brassica napus aleurone, with the highest level detected being approximately 47% of total fatty acids.